Construction of a multimodal esophageal cancer prognostic model with screening of key genes and investigation of their biological functions - Zhengsong Chang; Yiru Li; Mengyao Wang; Xin Zhang; Qiang Bai; Huan Luo; Pengyun Deng; Liping Yang; Xiaomei Li (Discover Oncology)
Abstract Purpose Despite decreased esophageal carcinoma incidence, its prognosis remains challenging. We aimed to develop a multimodal prognostic model to optimize treatment strategies and elucidate biological mechanisms of key regulatory genes. Methods Pivotal prognostic genes were screened using integrated bioinformatics and immunohistochemistry. A multimodal model combining PET/CT radiomics (metabolic tumor volume, SUV), clinicopathological parameters (lymph node metastasis, differentiation grade, infiltration depth), and molecular biomarkers was established and validated. Functional experiments and co-immunoprecipitation/transcriptomic sequencing explored biological roles and molecular networks. Results CASQ2 emerged as a key prognostic gene. The validated model integrated CASQ2 expression, radiomic features (MTV/SUV), and clinical staging, demonstrating high predictive accuracy. Functional assays confirmed that CASQ2 overexpression enhanced esophageal cancer cell proliferation and invasion. Mechanistically, CASQ2 activated AKT/PI3K signaling and disrupted calcium homeostasis, with protein interaction and transcriptomic analyses delineating its regulatory network. Conclusion We established a multimodal prognostic model incorporating molecular, radiomic, and clinical parameters, and identified CASQ2 as a critical regulator of esophageal carcinogenesis. CASQ2 likely drives tumor progression through AKT/PI3K signaling and calcium pathway dysregulation, offering dual therapeutic targets. This integrative approach advances personalized prognosis prediction and mechanistic understanding.